FINANCIAL SECURITY AS A KEY POINT OF VIEW IN BUILDING A MODERN FINANCIAL ARCHITECTURE (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2025)
The purpose of the article is to substantiate the influence of a multi-vector complex of external and internal factors on the financial security of an enterprise, to identify key elements of the formation of a reliable mechanism and to characterize the constituent determinants of the system of ensuring the financial security of business entities as a key reference point for the development of modern financial architecture. Financial security can be characterized as a certain level of independence, stability, and stability of the development of internal and external financial and economic systems, their ability to adapt in conditions of uncertainty and the impact of risks, the ability to ensure effective current functioning and prospective economic growth of business entities, taking into account the multi-vector influence of exogenous and endogenous factors. The level of financial security directly affects the level of financial condition of enterprises, determines the effectiveness of their financial and economic activities, therefore, special attention is required to study the complex of factors that affect the level of financial security, thanks to which it is possible to develop effective and justified management decisions. For successful and stable development in the long term, in order to protect, prevent and neutralize the effects of adverse and threatening factors, economic entities must systematically carry out a thorough analysis and forecast of the impact of exogenous and endogenous factors on the level of internal and external financial security. Financial security is an integral part and an important element of the formation of modern financial architecture, the purpose of which is to build an effective system to ensure a sufficient level of protection of the enterprise from the impact of internal and external threats. The article identifies and characterizes the key determinants of an effective system for ensuring the financial security of business entities, aimed at its formation, strengthening and further development: financial resources management subsystem; financial status and financial results management subsystem; financial, economic and investment and innovation potential management subsystem; market and specific risk management subsystem. The key guidelines for the formation of a reliable system for ensuring the financial security of Ukrainian enterprises in the conditions of war and post-war recovery of the national economy are identified. The development of an effective system of financial security of an enterprise as a key guideline in the concept of developing a modern financial architecture depends on a comprehensive approach that combines strategic planning and management, tactical and operational measures to respond to changes in the external and internal environments, monitoring and control of the effectiveness of the functioning of the constituent determinants of the security system, substantiation of alternatives and adjustment of management decisions, proactive response to risks and threats in conditions of uncertainty.
Keywords: financial security; financial architecture; security system; external and internal threats; uncertainty; financial and investment potential; financial risks